cAMP inhibits induction of interleukin 2 but not of interleukin 4 in T cells. - Novak, T J (1990)
In this report, we explore the nature of the inductive stimuli leading to expression of the divergently regulated lymphokines interleukin 2 (IL-2) and interleukin 4 (IL-4). Elevation of cAMP levels blocks IL-2 induction while sparing IL-4 induction. These effects are gene-specific, not cell-specific, and can be observed in the same cells. Transient transfection experiments using murine IL-2 regulatory sequences to drive expression of a reporter gene show at least part of the inhibition to act at the transcriptional level. The possible biological significance of these results is indicated by the observation that representative type 2 helper T-cell lines maintain significantly higher levels of cAMP per cell than a type 1 helper T-cell line. Fresh splenic CD4+ T cells, which preferentially make IL-2, have particularly low levels of cAMP per cell and a low capacity to elevate cAMP in response to forskolin. However, their response to forskolin increases significantly after several days of stimulation. These results suggest a potential link between differential cAMP regulation and the divergence of memory T cells into effector subsets.